Engineering students’ perceptions for engineers and engineering work - Bennett, Dawn; Maynard, Nicoleta; Kapoor, Ranjna; Kaur, Rajinder (School of Engineering & Advanced Technology, Massey University, Turitea Campus, Palmerston North 4442, 2014)
Background: Engineering is well ahead of many other disciplines in terms of establishing strong and evidence-based research and practice relating to employability. Despite this, there are high rates of student and graduate attrition in many countries. One possible reason for this is that students enter engineering study without a sense of motivation and commitment, and without understanding the realities of either their degree program or engineering work. Purpose: Educational institutions provide the learning foundation upon which competence for a professional engineering career is established; however, understanding how students position learning in relation to their future careers is a neglected area of research. Working with engineering students in their first semester of study, this research aimed to extend current understanding of students’ thinking about competencies, identity, self-efficacy, motivation, career preview, and both career aspirations and fears.Study Design: Twelve hundred first-year engineering students at an Australian university participated in in-class workshops in which they considered their future lives and work. Responses were coded using the Engineers Australia (EA) graduate competencies as a framework. In this paper we report findings from the first cohort of students (n=260), of whom 49% were international students with English as their second language. Results: Students most frequently characterised engineers in line with the EA competency Professional and Personal Attributes. Striking differences emerged between international and local (domestic) students’ perceptions of difference between the characteristics of engineers and their own attributes. These extended to Engineering Application Ability, Knowledge and Skill Base, and characteristics of engineers that are not EA competencies. Conclusions: Implications for engineering education include changes to the information that guides course and career choice; the role and impact of foundation-year, including career-oriented learning; and the structure and delivery of pedagogical approaches that explore engineering identity. In considering these implications, language and cultural diversity warrant further attention.